Efektivitas Sistem Akuntabilitas Kinerja Instansi Pemerintah (SAKIP) dalam Meningkatkan Kinerja ASN di Dinas Dukcapil Padang Pariaman - Syafirman, Syafirman; Syamsir, Syamsir (Policy, Law and Political Research Center, 2024)
This study aims to describe the effectiveness of the Government Agency Performance Accountability System (SAKIP) in improving the State Civil Apparatus (ASN) performance at the Population and Civil Registration Office of Padang Pariaman. This study uses a qualitative method with a descriptive approach, which is supported by the results of interviews. Based on the results of research applied to ASN at the Padang Pariaman Population and Civil Registration Office and analyzed using seven indicators put forward by Siagian, it can be concluded that the performance of ASN at the Padang Pariaman Population and Civil Registration Office is good. This is reflected in the effectiveness of programs from the center and nationally, performance effectiveness, and accuracy in analyzing and formulating educational policies that bring positive changes. In addition, clear goals and targets are in place. However, improved performance consistency and better evaluation are still needed.